Big data analytics capabilities and firm performance: An integrated MCDM approach - KILIÇ, HÜSEYİN SELÇUK (ELSEVIER SCIENCE INC, 2020)
This study explores the interdependence of big data analytics (BDA) capabilities and the impact of these capabilities on firm performance using an integrated multicriteria decision-making (MCDM) methodology. Drawing on a rich data set obtained from selected case study firms in Pakistan, three MCDM tools, namely, intuitionistic fuzzy decision-making trial and evolution laboratory (IF-DEMATEL), analytic network process (ANP), and simple additive weighting (SAW), are employed to assess the relative importance of BDA capabilities and the relationship of these capabilities with the firm performance. The results show that BDA capabilities are interdependent, and infrastructure capabilities are the highest-ranked among all, followed by management and human resource capabilities, respectively. The SAW results indicate an association between BDA capabilities and firm performance. Moreover, BDA capabilities are more strongly related to operational performance than to market performance.
Keywords: Big data analytics; Resource-based view; Dynamic capabilities; Multi-criteria decision-making; Firm performance; Emerging markets; INFORMATION-TECHNOLOGY CAPABILITY; DECISION-MAKING; BUSINESS ANALYTICS; NETWORK PROCESS; MEDIATING ROLE; ANP APPROACH; MANAGEMENT; SELECTION; DEMATEL; SYSTEM